2008
DOI: 10.1176/appi.ajp.2007.06111917
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala and Nucleus Accumbens Activation to Emotional Facial Expressions in Children and Adolescents at Risk for Major Depression

Abstract: Objective. Offspring of parents with major depressive disorder (MDD) face three-fold higher risk for MDD than offspring without a family history. Although MDD is a major cause of morbidity and mortality, neural correlates of risk for MDD remain poorly understood. This study compares amygdala and nucleus accumbens activation in children and adolescents at high and low risk for MDD under varying attentional and emotional conditions. Methods. Thirty-nine juveniles, 17 offspring of parents with MDD (high-risk grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
284
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 312 publications
(333 citation statements)
references
References 41 publications
36
284
7
Order By: Relevance
“…6,7 When a small volume correction was applied in a functional magnetic resonance imaging (fMRI) experiment, healthy adolescents with a family history of MDD displayed altered activation in the amygdala and nucleus accumbens when observing emotional faces. 8 Also, healthy monozygotic twins of patients with MDD showed greater activation in the left infer ior frontal gyrus during verbal encoding and retrieval. 9 These neural differences were discovered in spite of the absence of negative bias on a behavioural level, suggesting that susceptibility and associated changes can manifest themselves without behavioural signals.…”
Section: Introductionmentioning
confidence: 87%
“…6,7 When a small volume correction was applied in a functional magnetic resonance imaging (fMRI) experiment, healthy adolescents with a family history of MDD displayed altered activation in the amygdala and nucleus accumbens when observing emotional faces. 8 Also, healthy monozygotic twins of patients with MDD showed greater activation in the left infer ior frontal gyrus during verbal encoding and retrieval. 9 These neural differences were discovered in spite of the absence of negative bias on a behavioural level, suggesting that susceptibility and associated changes can manifest themselves without behavioural signals.…”
Section: Introductionmentioning
confidence: 87%
“…However, their role has not been fully understood. To date, a couple of studies have demonstrated associations between depression and reduced neural responses during the viewing of pleasant facial expressions and words (Epstein et al, 2006;Monk et al, 2008;Surguladze et al, 2005) and during the sight and taste of pleasant chocolate stimuli (McCabe et al, 2009;McCabe et al, 2012). These findings point to the general nature of reduced reward responsiveness in depression, beyond monetary rewards.…”
Section: Social Rewards In Depressionmentioning
confidence: 97%
“…Risch et al, 2009). Moreover, firstdegree relatives of MDD patients have been observed to exhibit greater amygdala activity in response to negative emotional material relative to participants at low-risk for MDD (Monk et al, 2008;van der Veen, Evers, Deutz, & Schmitt, 2007). The 5-HTTLPR S allele is associated with decreased transcriptional efficiency of the promoter (Lesch et al, 1996), and increased available synaptic 5-HT acting on excitatory 5-HT receptor subtypes (Rainnie, 1999).…”
Section: The Role Of Amygdala Function In Depressionmentioning
confidence: 99%
“…There is also abundant evidence to suggest that amygdala hyperactivity towards negative stimuli is related to long-term negative memory bias in depression (Hamilton & Gotlib, 2008). Importantly however, negatively-biased amygdala activity is also exhibited by non-depressed 5-HTTLPR S allele carriers Heinz et al, 2005;Lonsdorf et al, 2011;Pezawas et al, 2005) and first-degree relatives of MDD patients (Monk et al, 2008). Evidence suggests that modulatory effects of the amygdala on memory are absent during immediate recall (Bass et al, 2014(Bass et al, , 2012Claire et al, 2015), and only emerge at recall sessions at least 24-hours after immediate testing, inferring that the amygdala may depend on overnight consolidation mechanisms to exert its influence on long-term memory.…”
Section: The 'Affect Tagging and Consolidation' (Atac) Modelmentioning
confidence: 99%